The effect of different combinations of flaxseed, melatonin, gum acacia, and betaine on diabetic rats with adenine-induced chronic kidney disease - Al Za’abi, Mohammed; Al Suleimani, Yousuf; Ali, Haytham; Ali, Badreldin H.; Al Maskari, Raya (Frontiers in Pharmacology, 2025)
Diabetes mellitus (DM) and chronic kidney disease (CKD) are associated with significant morbidity and mortality. Their progression is driven by inflammation, oxidative stress, and apoptosis. In this study, we examined the effects of nine different combinations of gum acacia (GA), melatonin, betaine, and flaxseed—used in pairs or trios—on adenine-induced CKD in streptozotocin (STZ)-induced diabetic rats. Rats treated with adenine and STZ exhibited significant hyperglycemia and CKD manifestations such as elevated plasma levels of cystatin C and indoxyl sulfate, increased urinary levels of N-acetyl-β-D-glucosaminidase (NAG) and NAG/creatinine ratio, and reduced creatinine clearance. Additionally, there was a significant decrease in renalase activity and urine osmolality, alongside a significant increase in IL-1β, IL-6, and TNF-α levels and a decrease in IL-10 levels. Oxidative stress biomarkers including superoxide dismutase, glutathione reductase, total antioxidant capacity, and catalase activities were also significantly impaired. These findings were supported by histopathological changes consistent with CKD. Treatment with the combinations of two or three agents alleviated most of these changes to varying degrees. Notably, the GA–melatonin–betaine combination demonstrated the most significant improvement across all the parameters along with the preservation of the kidney tissue structure. These improvements may partially be explained by the enhanced glycemic control achieved by this combination, in addition to possible synergistic molecular, pharmacokinetic, and pharmacodynamic interactions. These findings support the potential of this combination to attenuate the progression of CKD in the setting of diabetes. However, further mechanistic studies, pharmacokinetic profiling, and long-term toxicity data are necessary to validate its efficacy and safety for clinical use.